Hope, home and insecurity: Gendered labours of resilience among the urban poor of Metro Cebu, the Philippines. (October 2021) - Ramalho, Jordana
This article traces the labours of hope embedded in the everyday social reproductive practices of urban poor homeowner association members in Metro Cebu, the Philippines. It explores how aspirations for housing and land tenure security and the (failed) promises of opportunity bound in the urban materialise in the narratives and activities of women and men living in informal settlements. I argue that the sociality of hope, which propels and sustains homeowner associations, produces gendered labours of resilience amidst everyday circumstances of poverty, uncertainty, risk and displacement. As I reveal, these care-based practices constitute expressions of hope that are driven by moral codes associated with the family, industriousness and service to others. These findings reinforce the utility of hope as an analytical lens in geographical studies; one which broadens conceptualisations of labour beyond economic production to include, in this case, the emotional embodiments and reproductive activities that underpin people's everyday resilience.